Penyelesaian Konflik Lahan antara Pemda DKI Jakarta dengan Warga: Pendekatan Perspektif Peacemaking Criminology (Studi Kasus CAP 16 Kampung) - Noor Azlin Tauchid (Jurnal Kriminologi Indonesia, 2020)
AbstractEviction is phenomenon that happens in city livelihood related to city and human life development. In practice, eviction could lead to conflicts and social injury in which it causes reactions from the victims. CAP 16 Kampung is one of the reactions, in which the victims started a coalition to demand their participation in city development. CAP 16 Kampung process that involves dialogs and participatory actions are in line with Peacemaking Criminology perspective. From Peacemaking Criminology approach, CAP 16 Kampung in the evicted Kampung Akuarium fares much better due the already existing empathy and their affirmation actions about their shared fate as evicted victims. The other kampung, Kampung Muara Baru that yet to be evicted doesn’t have the same degree of success because they didn’t share the same threat as Akuarium did and there is no solid affirmation from them due the lacks of empathy being built.Keywords: Forced Eviction, Social Injury, Social Movement, Peacemaking Criminology, CAP 16 Kampung